Silymarin Prevents Memory Impairments, Anxiety, and Depressive-Like Symptoms in a Rat Model of Post-Traumatic Stress Disorder - El-Elimat, Tamam; Alzoubi, Karem H.; AbuAlSamen, Mahmoud M.; Al Subeh, Zeinab Y.; Graf, Tyler N.; Oberlies, Nicholas H. (Planta Medica, 2019)
Post-traumatic stress disorder (PTSD) is a debilitating psychopathological disease that is triggered by exposure to traumatic events. It is usually associated with substantial comorbidities, such as cognitive impairment, anxiety, and depression. Silymarin has been recently reported to exert neuroprotective activities against neurodegenerative diseases such as Alzheimerʼs and Parkinsonʼs diseases. Herein, the beneficial effects of silymarin in ameliorating PTSD-like symptoms such as memory impairments, anxiety, and depression were evaluated using a single-prolonged stress (SPS) rat model of PTSD. Male Wistar rats were randomly assigned into four groups: control, silymarin, SPS, or SPS + silymarin. Rats were administrated silymarin, 100 mg/kg i. p. for 4 wk. Rats in all groups were tested for short- and long-term memory in the radial arm water maze (RAWM), for anxiety-like behaviors using the open field test (OFT) and elevated plus maze (EPM) test, and for depression-like symptoms using the tail suspension test (TST). Conventional analyses of the RAWM, EPM, OFT, and TST were conducted using analysis of variance. Additionally, the anxiety-related behavior parameters of the EPM and OFT were entered to principal component analysis. Regression scores based on the first two extracted components, which accounted for 61% of the variance, were indicative of the anxiolytic activity of silymarin. Collectively, the results suggest that silymarin treatment prevents SPS-induced long-term memory impairments, anxiety, and depressive-like symptoms in rat models.
Keywords: Compositae; milk thistle; post-traumatic stress disorder; principal components analysis; silymarin; Silybum marianum; single-prolonged stress